2013
DOI: 10.1155/2013/703626
|View full text |Cite
|
Sign up to set email alerts
|

Schiff Base Metal Derivatives Enhance the Expression of HSP70 and Suppress BAX Proteins in Prevention of Acute Gastric Lesion

Abstract: Schiff base complexes have appeared to be promising in the treatment of different diseases and disorders and have drawn a lot of attention to their biological activities. This study was conducted to evaluate the regulatory effect of Schiff base metal derivatives on the expression of heat shock proteins (HSP) 70 and BAX in protection against acute haemorrhagic gastric ulcer in rats. Rats were assigned to 6 groups of 6 rats: the normal control (Tween 20 5% v/v, 5 mL/kg), the positive control (Tween 20 5% v/v, 5 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
2
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 41 publications
1
2
0
Order By: Relevance
“…In the gastric mucosa, it has been reported that HSP70 has important cytoprotective functions in vitro and in vivo [ 32 ]. In accordance with several studies [ 33 35 ], the present finding showed remarkable upregulation of the expression of HSP70 in rats pre-treated with mushroom extracts. The HSP70 family functions as a molecular chaperone and reduces stress-induced denaturation and aggregation of intracellular proteins.…”
Section: Discussionsupporting
confidence: 93%
“…In the gastric mucosa, it has been reported that HSP70 has important cytoprotective functions in vitro and in vivo [ 32 ]. In accordance with several studies [ 33 35 ], the present finding showed remarkable upregulation of the expression of HSP70 in rats pre-treated with mushroom extracts. The HSP70 family functions as a molecular chaperone and reduces stress-induced denaturation and aggregation of intracellular proteins.…”
Section: Discussionsupporting
confidence: 93%
“…A previous study proved the essential role of HSP70 in the mucosal cytoprotection. 55 This effect may be prompted via the inhibition of the cell apoptotic process 56 through its chaperone function, other than that of the immune response. 57 An earlier study reported the critical involvement of HSP70 protein in the gastroprotection mechanisms against ethanol-induced gastric ulcer.…”
Section: Discussionmentioning
confidence: 99%
“…Bax/Bak forms oligomers on the outer mitochondrial surface and activates the caspase cascade (28). Studies have shown that programmed cell death and increased Bax protein expression play an important role gastric injuries induced by NSAID (29), ethanol (30,31) and water immersion-restraint stress (32).…”
Section: Discussionmentioning
confidence: 99%